Flexible lead-free Na0.5Bi0.5TiO3–EuTiO3 solid solution film capacitors with stable energy storage performances. (15th July 2020) - Guo, Fei; Shi, Zhifeng; Yang, Bo; Liu, Yaping; Zhao, Shifeng
Abstract: Flexible lead-free Na0.5 Bi0.5 TiO3 –EuTiO3 solid solution film capacitors were fabricated. The recoverable energy storage density and energy storage efficiency reach 65.4 J/cm 3 and 52%, respectively, due to the great insulation characteristic and relaxor behaviors. And the energy storage performances for the flexible solid solution films show excellent stabilities on temperature, frequency and bending endurance, especially, with bending endurance stability over 10 5 cycles. And the energy storage performances still remain great properties after delay of a month and another 10 5 cycles. This work provides a candidate for the flexible film capacitors with giant application potentials in wearable energy storage devices. Graphical abstract: Image, graphical abstract